Measurement of total bile acids in gastric juice. Issue 3 (March 1984) - Collins, B J; Watt, P C; O'Reilly, T; McFarland, R J; Love, A H
Abstract : An established method for the assay of total bile acids was validated for use in fasting and post-prandial gastric juice samples. Fasting and post-prandial intragastric bile acid concentrations were measured in 29 healthy volunteers, 15 patients after vagotomy and gastrojejunostomy (V and GJ) and 15 patients after vagotomy and pyloroplasty (V and P). Healthy female volunteers had higher post-prandial bile acid concentrations than age matched healthy males (p less than 0.02). Patients with V and GJ had higher fasting and post-prandial bile acid concentrations than age and sex matched control subjects (p less than 0.01). Patients with V and P had higher bile acid concentrations than control subjects only in post-prandial samples (p less than 0.05).